Competitive and/or Cooperative Interactions of Listeria monocytogenes With Bacillus cereus in Dual-Species Biofilm Formation - Alonso, Vanessa Pereira Perez; Harada, Andréia Miho Morishita; Kabuki, Dirce Yorika (Frontiers in Microbiology, 2020)
Microorganisms in dairy industries can form monospecies, dual-species, or multispecies biofilms, showing cooperative or competitive behaviors, which might contribute to the reduction of efficiency of cleaning and sanitization processes and eventually turn into a potential source of contamination. This study proposes to evaluate the behavior of Listeria monocytogenes in monospecies biofilms, cocultured with Bacillus cereus. The isolates were of dairy origin, and the selection occurred after studies of competition among species. The biofilm formations on AISI 304 stainless steel at 25°C in a stationary culture were analyzed to observe the cooperative or competitive interactions among species, as well as the effect of pre-adhered cells. Biofilm formation assays were performed in four experiments: Experiment 1: in the presence of strains of antagonistic substance producer B. cereus (+); Experiment 2: extract of the antagonistic substance of B. cereus; Experiment 3: pre-adhered cells of B. cereus; and Experiment 4: pre-adhered cells of L. monocytogenes. Subsequently, cooperative behavior was observed by scanning electron microscopy. The L. monocytogenes monospecies biofilm counts of greater than 5 log colony-forming units (CFU)/cm2 were also observed in dual-species biofilms in the presence of B. cereus (non-producers of antagonist substance), showing cooperative behavior between species. However, in the presence of antagonistic substance produced by B. cereus, the counts were lower, 1.39 and 1.70 log CFU/cm2 (p > 0.05), indicating that the antagonistic substance contributes to competitive interactions. These data are relevant for the development of new studies to control L. monocytogenes in the dairy industry.